Bibliographie der Bestimmungstabellen europäischer Insekten (1974-1978). - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1981)
This paper continues previous studies and lists with annotations the puplications with keys to European insects that appeared between 1974 and 1978.